The Divine Gaps between the Usuli and Akhbaris in Bahrain: Causes and Repercussions - Alrasheed, Rashed (Religions, 2020)
In any analysis of Bahrain’s political structure, it is fundamental to understand the relationship between the Usili, Akhbaris, and authority. This analysis includes an assessment of the implications of the differences between the Usili and Akhbaris, thus shedding light on the dynamic interaction between these players in local and external structures and clarifying the effect of ideology and identity on the ties of authority with Shi’a. Usuli and Akhbaris principles have incontrovertible implications for the political perceptions of Shi’a groups and elites with regard to their dealings with the government in Bahrain. These religious perceptions form part of the political equation involved in ensuring the convergence of authority with the Shi’a community. This paper considers how differences between the Usuli and Akhbaris have shaped the relation between authority and Shi’a in Bahrain.